Formulating Strategy Of Small Medium Enterprises Through Digital Transformation Post-Pandemic Covid-19 - Nuruni Ika K.W; Ignathia Martha; Nurkholish Majid (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study aims to formulate the right strategy for SMES to prepare for economic recovery after the COVID19 pandemic. The results of the research through SWOT analysis show that business actors are in a position to develop their business or the right strategy is growth strategy, which is carried out in the form of product development and marketing networks. Network marketing can be done by developing several digital applications that are not only marketplace-based but can also be done in the form of a website to introduce new brands and business models with a franchise system and partnerships with industry (Business to Business). Business development can also be done through e-wallet payment transaction tools and strengthening marketing networks through social media.